Proportion of Immediate Postpartum Anaemia and Associated Factors among Postnatal Mothers in Northwest Ethiopia: A Cross-Sectional Study - Asenake Abebaw; Temesgen Worku Gudayu; Bayew Kelkay (Anemia)
Background. Anaemia is a major global health problem, especially in developing countries. Postpartum anaemia hurts both maternal and newborn baby health. Anaemia in pregnancy is sufficiently emphasized; however, very little attention has been paid to postpartum anaemia in Ethiopia. Therefore, this study aimed to investigate the proportion of immediate postpartum anaemia and associated factors among postpartum mothers in Debre Markos Referral Hospital. Methods. Institutional-based cross-sectional study was conducted among 424 study participants from August 1st to October 30th, 2019. A systematic random sampling technique was employed to select the study participants. Data were collected through both face-to-face interview and maternal chart review by using a pretested questionnaire. Data were cleaned, coded, and entered using Epi Data version 4.6.0.0 and then exported to SPSS version 24 for analysis. First, binary logistic regression was applied to identify candidate variables for multivariable regression. Then, variables at p value <0.2 were entered into a multivariable logistic regression to control possible confounders. Finally, variables at p value <0.05 were considered as statistically significant. Results. The proportion of immediate postpartum anaemia was 24.3%. Frequency of antenatal care (ANC) visits <4 times [AOR = 2.40; 95% CI (1.29, 4.43)], antepartum haemorrhage (APH) [AOR = 5.08; 95% CI (1.91, 13.55)], postpartum haemorrhage (PPH) [AOR = 4.47; 95% CI (2.25, 8.88)], giving birth assisted by instruments (vacuum or forceps) [AOR = 3.99; 95% CI (1.42, 11.23)], poor adherence to iron and folic acid (IFA) [AOR = 2.52; 95% CI (1.06, 6.04)], and midupper arm circumference (MUAC) <23 cm [AOR = 3.25; 95% CI (1.87, 5.65)] were the predictors. Conclusion. The proportion of immediate postpartum anaemia was a moderate public health concern. ANC, APH, PPH, mode of delivery, adherence to IFA supplementation, and MUAC measurement were the factors affecting the magnitude of anaemia. Therefore, interventions that would address the above mentioned factors need to be implemented.